Effect of dried extract Curcuma zedoria. Rosc. orally on the some parameters of kidney function of male rat - Sumarny, Ros; Parodi, Dwi; ., Darmono (Indonesian Journal of Pharmacy, 2006)
Curcuma zedoria Rosc. has been used empirically for cancer medicine and usually used for long periods. The aim of this study is to assess the effects of dried extract Curcuma zedoria. Rosc. orally on kidney function of male rat for 12 weeks exposure. Eighty male rat (180-200g) were divided into four group, group 1 as a control group, group 2, 3 and 4 were given 9mg/200g body weight, 18 mg/200g bw and 27mg/200g bw respectively. Dried extract of Curcuma zedoria Rosc. was given daily for 12 weeks periods, serum, urine, and kidney samples were collected by killing of 5 rats in each group on week 4, 8, 12 and 16 respectively. Serum, and urine samples were analyze for creatinine,pH, specific gravity and morphological and histological of the kidney were also observed respectivelyThe results indicated that serum, and creatinine content, pH and specific gravity of urine were not significantly different between control and treatment group of dosage and time of exposure (P>0.05). From the results can be concluded that dried Curcuma zedoria Rosc. given orally at the dosage up to 27mg/200g bw for long periods was safe for male rats and safely to use as a traditional medicine given at the long periods of time.Key words: Curcuma zedoria. Rosc, urine chemical, kidney.